2021
DOI: 10.21111/atj.v5i1.5304
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Penggunaan Bahan Baku Terhadap Karakteristik Vegetable Abon

Abstract: Floss is a food that is generally made from meat, but floss can also be developed from local food ingredients that have fiber-like meat such as kluwih, breadfruit, and jackfruit. Making floss from local food can increase food diversification and its economic value. The purpose of this study was to determine the sensory and chemical characteristics of artificial flosses from kluwih, breadfruit, and jackfruit. This research used a completely randomized design with 3 types of the raw materials: kluwih, breadfruit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 1 publication
0
0
0
Order By: Relevance
“…In this study, the main raw material used for vegetable floss is breadnut. Research conducted by Mirratunisya et al (2021) (6) indicated that vegetable floss made from breadnut was preferred over floss made from breadfruit and young jackfruit. Breadnut itself has high carbohydrate content with fibrous texture similar to meat.…”
Section: Emergence Of Technical Solution Conceptsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, the main raw material used for vegetable floss is breadnut. Research conducted by Mirratunisya et al (2021) (6) indicated that vegetable floss made from breadnut was preferred over floss made from breadfruit and young jackfruit. Breadnut itself has high carbohydrate content with fibrous texture similar to meat.…”
Section: Emergence Of Technical Solution Conceptsmentioning
confidence: 99%
“…The floss product cooking process typically involves raw material preparation, mixing raw materials with seasonings, and then frying. The production of vegetable floss follows a modified process based on Mirratunisya et al (2021) (6). The process begins with boiling breadnut for 45 minutes, followed by crushing and mixing it with seasonings.…”
Section: Emergence Of Technical Solution Conceptsmentioning
confidence: 99%
See 1 more Smart Citation